Implementation of strengthening the function of agricultural extension in East Bolaang Mongondow Regency - Malonda, Happy Eike; Tumbel, Goinpeace H.; Siwij, Devie S. R. (Technium Social Sciences Journal, 2025)
The purpose of this research is to analyze how the implementation of strengthening the function of agricultural extension and the factors that influence the effectiveness of agricultural extension based on the phenomenon of Agricultural Extension problems in East Bolaang Mongondow Regency in accordance with the Minister of Agriculture Regulation No. 27 of 2023. This research used qualitative research methods. The number of informants was 10 people determined by purposive sampling technique. The data collection techniques used were observation, interview, and document study. The results showed that the implementation of strengthening the function of agricultural extension in East Bolaang Mongondow Regency which focuses on four main indicators in accordance with the Minister of Agriculture Regulation No. 27 of 2023, namely strengthening working relationships, providing and increasing the capacity of extension personnel, utilizing technology and information, and ensuring the availability of infrastructure and facilities, has contributed positively to the success of extension services. The four indicators play an important role: (1) Strengthening working relationships shows good collaboration, although strengthening synergies is still needed; (2) Provision and capacity building of extension personnel has been carried out through training, but still requires a sustainable program; (3) The use of technology and information has begun to be applied, but increasing accessibility and technical skills is still a challenge; (4) Guaranteeing the availability of basic infrastructure and facilities has been carried out, but it is not yet fully adequate and requires further support. Factors influencing the implementation of strengthening the extension function include government policies, human resources, supporting infrastructure and facilities, effective communication, inter-stakeholder collaboration, and agricultural technology and innovation.